Intercompreensão na escrita de línguas-culturas indígenas: o caso da família Jê - QUARESMA, Francinete de Jesus Pantoja (Universidade Federal do Pará, 2020)
Bordering on the extinction, Indigenous languages, survivors of the nineteenth century, search for alternatives for their preservation, not only in the description of languages, but also in indigenous school education, through effective teaching-learning methodologies that assist indigenous teacher practice in the classroom. The intercomprehension between related languages is a methodology of language teaching, applied in Europe expounding satisfactory results when developing students’ strategies of linguistic transferences and autonomy of learning from the reading of written texts in languages belonging to the same linguistic family, allowing the speaker of one language to establish interaction, in their mother tongue, with speakers of other languages. Among the indigenous people of Parkatêjê, Mẽbẽngôkre and Tapajuna ethnic groups, intercomprehension appears as a possibility for the development of the linguistic repertoire of indigenous speakers. To do so, it is necessary to instrumentalize the indigenous teacher in this methodology, so that he can adopt it in his native language classes. This, therefore, is the purpose of this study. The theoretical basis for this work is based on the Description of Indigenous Languages and Applied Linguistics, especially in the studies of European researchers. Thus, we discuss this issue from the perspective of Rodrigues (1993, 1999, 2003), Seki (2000), Cuq (2003), Escudé and Janin (2010), QECR (2001; 2007) and Hugues (2016). The methodology applied for the accomplishment this study has its ground based upon bibliographical research.